2018
DOI: 10.1038/s41598-018-30197-z
|View full text |Cite
|
Sign up to set email alerts
|

Heavy metals in Yinma River sediment in a major Phaeozems zone, Northeast China: Distribution, chemical fraction, contamination assessment and source apportionment

Abstract: Yinma River is a typical river in the major Phaeozems zone of Northeast China. It has been suffering an increasing environmental pressure from heavy metal contamination due to the rapid development of population, social-economy and urbanization as well as long term over cultivation. This study investigated the spatial distribution, chemical fraction of heavy metals (Cu, Pb, Zn, Cr, Cd, Ni, As, and Hg) in sediments of Yinma River based on BCR procedure, assessed the contamination level, and identified their sou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
34
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(38 citation statements)
references
References 51 publications
3
34
0
1
Order By: Relevance
“…It is also important to identify the sources of this pollution in order to establish an effective program of measures. In many previous studies, successful results have been obtained using multivariate analyses, which are known to be effective tools for determining the sources of heavy metal pollution in sediment [62][63][64][65] .…”
Section: Sediment Pollution Indices Various Pollution Indices For Asmentioning
confidence: 99%
“…It is also important to identify the sources of this pollution in order to establish an effective program of measures. In many previous studies, successful results have been obtained using multivariate analyses, which are known to be effective tools for determining the sources of heavy metal pollution in sediment [62][63][64][65] .…”
Section: Sediment Pollution Indices Various Pollution Indices For Asmentioning
confidence: 99%
“…Wind easily transfers the polluted sediment particles as dust storms and the pollution emission occurs naturally. Hence, analysis of the surface sediments on the playa can reasonably reflect the composition, toxicity and the pollution rate of dust storms 20,21 . Although, some studies have been reported in this respect, to the best of our knowledge, there are currently no published papers discussing the heavy metal analysis of the sediment of Jazmurian playa, This is the first study to examine the contamination of sediments of a basin dried due to climatic variations and human activities.…”
mentioning
confidence: 99%
“…Pencemaran lingkungan, terutama di ekosistem perairan, adalah salah satu masalah lingkungan terpenting pada saat ini. Pencemaran dalam ekosistem perairan disebabkan oleh berbagai polutan seperti logam berat termasuk Cr(VI) (Duruibe et al, 2007;Kyzas et al, 2014;Guan et al, 2018). Pencemaran pada ekosistem perairan menyebabkan degradasi ekosistem perairan secara bertahap.…”
unclassified